A composite indicator for short-term diffusion forecasts of renewable energy technologies – the case of Germany. Issue 1 (February 2016) - Boie, Inga; Ragwitz, Mario; Held, Anne
This paper investigates the impact of energy policy and the regulatory environment on the deployment of technologies based on renewable energy sources in Germany and presents a model to forecast future renewable energy technology diffusion. Our concept is based on the development of a composite indicator for renewable energy diffusion with a focus on wind energy (onshore) and photovoltaic. The approach has three major components: in-depth, semi-structured interviews with renewable energy developers and energy sector stakeholders to identify the major drivers and barriers (determinants) for renewable energy diffusion in the case study country; an EU-wide, questionnaire-based survey to understand the relevance (weights) of the individual determinants; and an analysis of past renewable energy diffusion patterns resulting in the deduction of a model for short-term renewable energy technology diffusion forecasts. Results demonstrate the substantial impact of economic and non-economic framework conditions on the diffusion of photovoltaic and wind energy in Germany. Furthermore, the use of composite indicators for renewable energy technology diffusion analyses proves to be a promising approach.